Implementation of a Targeted Technologic Screening Tool to Increase Pneumococcal Vaccine Uptake in Health-System Retail Pharmacies: A Quality Improvement Initiative - Annika Skogg; Alicia Zagel; R. May O'Donnell; Ann Philbrick; Mary Nelson; Allyson Schlichte; Kassie Klasen (INNOVATIONS in Pharmacy)
Background/Purpose: Pneumococcal vaccine rates among eligible adults are lower than desired. Recently, pneumococcal vaccination guidelines for adults were updated to include new pneumococcal conjugate vaccines (PCV20), taking into consideration age, underlying risk factors, and previous vaccine status. To respond to PCV undervaccination and help clarify the new guidelines, this project sought to develop a targeted pneumococcal vaccine screening tool and pop-up alert within retail pharmacies across a large health system with the goal of increasing rates of PCV20 vaccination.